PENGARUH KUALITAS KEHIDUPAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI PADA BENGKEL RESMI SEPEDA MOTOR HONDA DI KECAMATAN SUMBERSARI KABUPATEN JEMBER - Mataram, Adrian Suryo; Handriyono, Handriyono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
Abstract: Honda official workshop (AHASS) is a maintenance and repair service company for motorcycle products of Honda. To fulfill customers demand, the company management tries to improve employee performance in order to make their consumers satisfied with the offered service. The objectives of this research are to significantly examine the direct influence of quality of work life and work satisfaction on employee performance and the indirect influence of quality of work life and work satisfaction on employee performance through organizational commitment. This is an explanatory research with the sample consists of 50 (fifty) employees of Honda official workshops in Sumbersari District, Jember. Data were analyzed using path analysis with SPSS 19. The results show that quality of work life has a positive and significant effect on employee performance and organizational commitment; work satisfaction has a positive and significant effect on employee performance and organizational commitment; and organizational commitment has a positive and significant effect on employee performance. Keywords: Quality of Work Life, Work Satisfaction, Organizational Commitment, and Performance.